SYNTHESIS, CHARACTERIZATION AND CATALYTIC BEHAVIOUR OF SPECIAL TYPE OF SILICO ALUMINO-PHOSPHATE WITH OPAL STRUCTURE (Journal of Sciences, Islamic Republic of Iran)
In this study a special type of silicoaluminophosphate with opal structure (Opal-SAPO) was prepared under microwave condition using tetraethylorthosilicate (TEOS), triethanolamine (TEA), aluminiumisopropoxid and phosphoric acid 85%. The product was characterized by X-ray diffraction (XRD), thermogravimetric (TGA) and Fourier Infrared Spectroscopy (FTIR).The crystalline product showed a good activity and selectivity for regeneration of methylethylketone, benzaldehyde, and cyclohexanone from their semicarbazones derivatives.